2015
DOI: 10.1093/glycob/cwv017
|View full text |Cite
|
Sign up to set email alerts
|

Sialyltransferases with enhanced legionaminic acid transferase activity for the preparation of analogs of sialoglycoconjugates

Abstract: Legionaminic acids (Leg) are bacterial analogs of neuraminic acid, with the same stereochemistry but different substituents at C5, C7 and C9. Hence they may be incorporated into useful analogs of sialoglycoconjugates, and we previously reported two sialyltransferases that could utilize cytidine monophosphate (CMP)-Leg5Ac7Ac for preparation of Leg glycoconjugates, which were resistant to sialidases [Watson DC, Leclerc S, Wakarchuk WW, Young NM. 2011. Enzymatic synthesis and properties of glycoconjugates with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…In conclusion, our results show it is possible to produce Leg5Ac7Ac analogs of both glycolipids and glycoproteins with the two mammalian sialyltransferases. These are all considerably larger substrates than the ones we examined previously [1,2] so their successful modification extends the scope of these reactions to more biologically interesting substances, which was not possible with the bacterial sialyltransferases. However the recent finding of natural antibodies to legionaminic acid in human sera [21] rules out their use as therapeutics, though its known derivatives such as the 5-acetamidino form [22] may not be as reactive.…”
Section: Modification Of Interferon-α2bmentioning
confidence: 88%
“…In conclusion, our results show it is possible to produce Leg5Ac7Ac analogs of both glycolipids and glycoproteins with the two mammalian sialyltransferases. These are all considerably larger substrates than the ones we examined previously [1,2] so their successful modification extends the scope of these reactions to more biologically interesting substances, which was not possible with the bacterial sialyltransferases. However the recent finding of natural antibodies to legionaminic acid in human sera [21] rules out their use as therapeutics, though its known derivatives such as the 5-acetamidino form [22] may not be as reactive.…”
Section: Modification Of Interferon-α2bmentioning
confidence: 88%
“…[8] Leg5,7Ac 2 is activated by ac ytidine 5'-monophosphate-Leg5,7Ac 2 (CMP-Leg5,7Ac 2 )s ynthetase [3] to provide CMP-Leg5,7Ac 2 as the glycosyltransferase donor for the synthesis of desired structures. Although an ative Leg5,7Ac 2 glycosyltransferase has yet to be identified, several mammalian and bacterial sialyltransferases have been tested for catalyzing the transfer of Leg5,7Ac 2 from CMP-Leg5,7Ac 2 to galactosides.P orcine ST3Gal I, human ST6Gal I, [9] Pasteurella multocida sialyltransferase 1( PmST1), [10] and Neisseria meningitides MC58 a2-3-sialyltransferase [11] showed reasonable activity in forming Leg5,7Ac 2 -glycosides.Nevertheless,these enzymatic syntheses relied on ac omplex process to produce CMP-Leg5,7Ac 2 either from UDP-GlcNAc by multiple enzymes [12] in vitro with chemical acetylation of the 4-amino group [10] or from Leg5,7Ac 2 produced de novo using Escherichia coli engineered with combined biosynthetic pathways from Saccharomyces cerevisiae, Campylobacter jejuni, [13] and Legionella pneumophila. [14] Herein we show that aversatile library of a2-3-and a2-6linked Leg5,7Ac 2 -glycosides can be produced readily from chemically synthesized 2,4-diazido-2,4,6-trideoxymannose (6deoxyMan2,4diN 3 )a sachemoenzymatic synthon in highly efficient one-pot multienzyme (OPME) sialylation systems [15] using commercially available enzymes with downstream chemical derivatization.…”
mentioning
confidence: 99%
“…Previous mutagenesis studies by our lab and others indicated that M144 of PmST1 and its homologous residues in other GT80 STs are a multifunctional “hotspot,” and that mutations at this position can greatly impact donor hydrolysis activity, sialidase activity, sialyltransferase activity, donor specificity, and acceptor specificity. 45, 55 Therefore we hypothesized that screening a PmST1 P34H/M144X saturation library might reveal a more reactive α2–6ST.…”
Section: Resultsmentioning
confidence: 99%